A new Parakneria Poll 1965 (Gonorhynchiformes: Kneriidae), 'Mikinkidi' from the Upper Lufira Basin (Upper Congo: DRC): Evidence from a morphologic and DNA barcoding integrative approach. Issue 1 (29th November 2022) - Kiwele Mutambala, Pacifique; Abwe, Emmanuel; Schedel, Frederic D. B.; Chocha Manda, Auguste; Schliewen, Ulrich K.; Vreven, Emmanuel J. W. M. N.
Abstract: A new species, Parakneria alytogrammus, is described from the main stream of the Upper Lufira River. This species is easily distinguished from its congeners from the Congo Basin by its unique colouration, consisting of a low number of transversal bands on each of the caudal‐fin lobes, 2 ( vs. 3–5) and the presence of an uninterrupted lateral mid‐longitudinal black band in fresh and preserved specimens ( vs. absent). In addition, the new species differs from its Upper Lualaba congeners by the narrow width of its pectoral‐fin base, 4.8–5.6% L S [ vs. wider, 8.2–10.1% for P. lufirae, 8.6% L S for P. damasi (holotype), and 7.6–7.9% L S for P. thysi ]. Finally, it differs from the only species currently known from the Luapula‐Mweru system, P. malaissei, by having a short post‐dorsal distance, 36.4–36.6% L S ( vs. longer, 38.6–41.1% L S ) and a short post‐pelvic distance of 40.0–40.6% L S ( vs. longer, 41.4–44.1% L S ). Mitochondrial DNA‐haplotypes of P. alytogrammus sp. nov. form a clade, which is sister to the P. thysi clade, and from which it diverges by a genetic (Kimura 2‐parameter and uncorrected p ) distance of 0.7% in the COI‐barcoding locus. The Upper Lufira, one of the sub‐basins of the Upper Congo Basin, remains poorly explored relative to its fish fauna. In contrast, the region is well explored with regard to its mineral wealth. Unfortunately, mining exploitation is carried out in the region without proper concern for the environment. Thus, the discovery of this new species for science calls for increased protection and aquatic biodiversity exploration in this mining region.